Rapid determination of histamine in fish by thin-layer chromatography-image analysis method using diazotized visualization reagent prepared with p-nitroaniline - Yu, Hui; Zhuang, Daina; Hu, Xingjuan; Zhang, Shuang; He, Zhiyong; Zeng, Maomao; Fang, Xubo; Chen, Jie; Chen, Xiaoe (Analytical methods, 2018)
A novel analytical method for rapid determination of histamine in fish involves methanol extraction, manual spotting, thin-layer chromatography (TLC) for less than 15 min, visualization by diazotized p -nitroaniline reagent, and quantitation by image analysis using the ImageJ software. Following this procedure, histamine can be successfully detected and completely separated from other biogenic amines and diazonium reagent's positive compounds. Moreover, this method does not require any expensive reagent and instrument as well as any tedious sample pre-treatment. The characterization of this method revealed good specificity, linearity in the range of 100-1200 ng per spot (adjusted R -square = 0.9987), precision (relative standard deviation, 1.07-2.76%), accuracy (with a trueness of 1.76-6.22%), recovery rate (93.78-98.24%), limit of detection (23.49 ng per spot), and limit of quantitation (78.29 ng per spot). The proposed method is simpler, faster and less expensive than HPLC and the previously reported TLC/HPTLC. Therefore, this method has the potential to be adapted by aquatic enterprises and aquatic market supervision commissions for monitoring the quality of seafood products during processing, storage, and sales. A novel analytical method for rapid determination of histamine in fish involves methanol extraction, manual spotting, thin-layer chromatography (TLC) for less than 15 min, visualization by diazotized p -nitroaniline reagent, and quantitation by image analysis using the ImageJ software.